Limiting distributions of the solutions of the many-dimensional Bürgers equation with random initial data. II - Leonenko, N. N.; Orsingher, E.; Rybasov, K. V. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
We find non-Gaussian limiting distributions of the solutions of the many-dimensional Burgers equation with the initial condition given by a homogeneous isotropic Gaussian random $χ^2$-type field with strong dependence.